A chemical study of M67 candidate blue stragglers and evolved blue stragglers observed with APOGEE DR14 - Bertelli Motta, Clio; Pasquali, Anna; Grebel, Eva K.; Caffau, Elisabetta (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Within the variety of objects populating stellar clusters, blue straggler stars (BSSs) are among the most puzzling ones. BSSs are commonly found in g
Gesehen am 25.01.2019